Cloud technologies in the professional training of computer science students - Yu. V. Tryus (Academy of Cognitive and Natural Sciences, 2013)
Under the conditions of intensive development of information society, the actual problem is the training of future IT specialists, who should not only maintain the existing level of information technology, but also be ready to use and develop the next generations of computer equipment and information and communication technologies. The peculiarities of training future IT-specialists in universities include the fact that: - domestic and international IT labor market offers many vacancies for IT-specialists, with employers, in addition to high-quality professional training, focus on the ability of computer graduates to learn quickly, the ability to work in a team and communication skills, including Anguillian; - technologies in the sphere of future professional activity of IT-specialists change rapidly, especially software; - Higher education institutions in the training of IT-specialists feel intense competition in the market of educational services from both corporate training in IT-firms, and paid and free courses on current issues in the field of ICT.